2014
DOI: 10.3109/10717544.2014.932862
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization and in vitro activities evaluation of solid lipid nanoparticles based on PEG-40 stearate for antifungal drugs vaginal delivery

Abstract: The present article reports the preparation, characterization and performance evaluation of solid lipid nanoparticles (SLNs) based on polyoxyethylene-40 stearate (PEG-40 stearate) for the administration of antifungal agents such as ketoconazole and clotrimazole. These nanoparticles could be useful in the treatment of vaginal infections sustained by Candida albicans. In particular, PEG-40 stearate was made to react with acryloyl chloride in order to introduce an easily polymerizable moiety for the creation of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…The SLNs have been obtained by the technique of the microemulsion [16][17][18][19][20][21][22][35][36][37]. The obtained ester, in the presence or in the absence of progesterone, was melted in a beaker at a temperature of about 70°C (temperature value higher than the melting temperature of the lipid).…”
Section: Preparation Of Solid Lipid Nanoparticles (Slns)mentioning
confidence: 99%
See 2 more Smart Citations
“…The SLNs have been obtained by the technique of the microemulsion [16][17][18][19][20][21][22][35][36][37]. The obtained ester, in the presence or in the absence of progesterone, was melted in a beaker at a temperature of about 70°C (temperature value higher than the melting temperature of the lipid).…”
Section: Preparation Of Solid Lipid Nanoparticles (Slns)mentioning
confidence: 99%
“…Solid lipid nanoparticles (SLNs) are colloidal drug delivery systems able to transport lipophilic or hydrophilic molecules and can be obtained using different preparation approaches [12][13][14][15][16][17][18][19][20][21]. They are an alternative drug delivery system to other colloidal carriers, e.g., emulsions, liposomes, and polymeric nanoparticles, and very useful for the encapsulation, in particular, of drugs with poor water solubility such as progesterone [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PEG-40 stearate is a synthetic polyethyleneglycol lipid based on stearic acid, with 18 carbons in its chain, and glyceryl behenate is a lipid formed by glycerides of 22 carbon fatty acid and behenic acid. Previous reports indicated that stearic acid was able to emulsify with both poloxamer 188 and 407 in presence of PEG 4000 for lopinavir-loaded solid lipid nanoparticle formation, whereas glyceryl behenate, more hydrophobic, only emulsified with poloxamer 407, used herein, which has a larger proportion of more hydrophobic polyoxypropylene portion than polyoxyethylene [21][22][23]. Noteworthy, the use of these delivery systems for tyrosinase inhibition is an innovative aspect addressed herein.…”
Section: Introductionmentioning
confidence: 97%
“…Solid lipid nanoparticles (SLNs) which were introduced in 1991 are used as alternative nanocarrier systems to traditional colloidal carriers, such as emulsions, liposomes and polymeric nanoparticles (Cassano et al, 2014;Rostami et al, 2014;Pandey et al, 2015). Compared with these traditional colloidal carriers, SLNs offer the following advantages: improved biocompatibility; controlled drug release; potential for site-specific drug delivery, etc.…”
Section: Introductionmentioning
confidence: 99%